Pengaruh Pemahaman Nilai Anti Korupsi Terhadap Prilaku Mahasiswa Dalam Melaksanakan Ujian Perkuliahan - Nurhuda, Dede Yuda Wahyu (Penerbit Widina, Widina Media Utama, 2025)
Corruption is an extraordinary crime, the impact of which has been felt by all levels of Indonesian society, to eradicate corruption requires a strategy and great attention from all community components. One of the efforts to eradicate corruption is preventive, namely by providing an understanding of corruption to the community through education, including anti-corruption education in universities. The research was conducted in study programmes that have implemented Anti-Corruption Education courses, namely Diploma three Health Analyst and Diploma three Nursing at Bakti Tunas Husada University. This research was conducted using descriptive correlation method, with data collection and analysis through survey. where the investigation paid attention to the level of student understanding of anti-corruption values and student behaviour in the implementation of lecture exams. The purpose of this study is to determine the level of understanding of anti-corruption values of students and the actualisation of these values. From the results of the study, it was found that students understood the anti-corruption value material delivered through the anti-corruption culture education course and the attitudes and behaviour of students during the exam strongly reflected anti-corruption values. The results concluded that the understanding of anti-corruption values of students was positively and significantly related to the behaviour of students when carrying out the exam.ABSTRAKKorupsi merupakan kejahatan luar biasa (extraordinary crime), yang dampaknya sudah dirasakan oleh semua lapisan masyarakat Indonesia, untuk memberantas korupsi memerlukan strategi dan perhatian yang besar dari semua komponen masyarakat. Salah satu upaya pemberantasan korupsi bersifat preventif yaitu dengan memberikan pemahaman terkait korupsi kepada masyarakat melalui Pendidikan termasuk Pendidikan anti korupsi di perguruan tinggi. Penelitian dilaksanakan pada Program Studi yang telah melaksanakan perkuliahan mata kuliah Pendidikan Anti Korupsi yaitu Diploma tiga Analis Kesehatan dan Diploma tiga Keperawatan Universitas Bakti Tunas Husada. Penelitian ini dilaksanakan dengan metode deskriptif korelasional, dengan pengumpulan dan analisa data melalui survey. Di mana dalam penyelidikannya memperhatikan tingkat pemahaman mahasiswa terdapat nilai anti korupsi dan terhadap prilaku mahasiswa dalam pelaksanaan ujian perkuliahan. Tujuan dari penelitian ini adalah untuk mengetahui tingkat pemahaman nilai anti korupsi mahasiswa dan aktualisasi nilai tersebut. Dari hasil penelitian didapatkan bawah mahasiswa memahami materi nilai anti korupsi yang disampaikan melalui matakuliah Pendidikan budaya anti korupsi serta sikap dan prilaku mahasiswa saat ujian sangat mencerminkan nilai anti korupsi. hasil penelitian menyimpulkan bahwa pemahaman nilai anti korupsi mahasiswa berhubungan positif dan signifikan dengan perilaku mahasiswa saat melaksanakan ujian.